Outcomes of an Open Autologous Osteochondral Plug Graft for Capitellar Osteochondritis Dissecans: Time to Return to Sports. (September 2014) - Maruyama, Masahiro; Takahara, Masatoshi; Harada, Mikio; Satake, Hiroshi; Takagi, Michiaki
Background: Autologous osteochondral plug grafts have been used for capitellar osteochondritis dissecans (OCD), and good clinical results have been described. However, little is known about the optimal timing of return to sports. Purpose: To investigate the clinical outcomes of open autologous osteochondral plug grafts for capitellar OCD and to address the timing of return to sports. Study Design: Case series; Level of evidence, 4. Methods: Thirty-three male patients with a mean age at the time of surgery of 13.6 years (range, 11-17 years) and with advanced lesions of capitellar OCD underwent a procedure using open autologous osteochondral plug grafts. All patients played baseball, and the lesion affected their throwing side. Thirteen lesions were arthroscopically classified as International Cartilage Repair Society (ICRS) OCD III and 20 lesions as ICRS OCD IV. The mean size of the lesions (sagittal × coronal) was 16 × 14 mm. One to 3 osteochondral plug grafts, with a mean diameter of 7 mm (range, 5-9 mm), were harvested from the lateral femoral condyle and transplanted to the defects. Patients were allowed to begin throwing after 3 months and to return to sports after 6 months. The mean follow-up was 28.4 months (range, 12-76 months), during which elbow pain, Timmerman and Andrews scores, return to sports, and radiographs were evaluated. Results: After surgery, 30 patients (91%) had no elbow pain, and 3 patients (9%) had occasional mild throwing pain. The mean total arc of elbow motion increased significantly from 116° to 133° ( P < .05). The mean Timmerman and Andrews score improved significantly from 143 to 190 ( P < .05). All except 2 patients returned to a competitive level at which they had previously played after a mean of 6.9 months (range, 6-14 months). One patient chose another sport, and another retired from baseball after high school graduation. All patients achieved graft incorporation, and there was no postoperative enlargement of osteophytes on radiographs. One patient had mild anterior knee pain at the donor site during exercise. The remaining patients had no knee pain. The mean Lysholm score was 99.8. Conclusion: The results of this study indicate that an open autologous osteochondral plug graft allows a return to the previous competitive level of throwing by a mean of 7 months postoperatively.